Proses Pembuatan Busana Feminime Romantic Khas Belanda Dengan Variasi Pita Renda Dan Ruffle - Edi Suwasana; Sebtaribah (Garina, 2023)
Romantic clothing is clothing made to create a romantic impression by applying variations of ribbons, lace and ruffles. The selection of materials uses vintage colors so that the clothes seem classic and elegant. The problem in making this final project is how the process of making Dutch romantic feminime clothing with variations of lace ribbons and ruffles. The goal is to find out the process of making typical Dutch romantic feminime clothing with variations of ribbons, lace and ruffles. The methods used are data collection methods, namely library methods, observation methods, documentation methods and data analysis. The process of making typical Dutch romantic feminime clothing with variations of ribbons, lace and ruffles is making designs, preparing tools and materials, taking measurements, making patterns, breaking patterns, putting patterns on fabric, cutting, pasting upholstery materials, merader. Next sew fashion from putting components together, furing, skirts, sewing lace on bell sleeves, making variations of ribbons, lace and ruffles and making hats. This clothing has the characteristics of Noni in the Dutch royal era. Inspired by texel sheep that have thick meat and dense fur depict prosperity. Suggestions in making ruffles for making ruffles using wrinkle shoes according to the sewing machine, so that the wrinkle results are equal and balanced. During the process of sewing rasfur fabric, you should use a tool used to turn the fur so that it does not fold so that the surface of the feather remains balanced.